2016
DOI: 10.4103/2152-7806.191079
|View full text |Cite
|
Sign up to set email alerts
|

Extreme lateral lumbar interbody fusion: Do the cons outweigh the pros?

Abstract: Background:Major factors prompted the development of minimally invasive (MIS) extreme lateral interbody fusion (XLIF; NuVasive Inc., San Diego, CA, USE) for the thoracic/lumbar spine. These include providing interbody stabilization and indirect neural decompression while avoiding major visceral/vessel injury as seen with anterior lumbar interbody fusion (ALIF), and to avert trauma to paraspinal muscles/facet joints found with transforaminal lumbar interbody fusion (TLIF), posterior lumbar interbody fusion (PLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 30 publications
0
40
2
Order By: Relevance
“…[ 26 , 27 ] Despite these advantages, XLIF has been also associated with a considerably higher frequency of neurological complications and other major morbidity. [ 28 ] XLIF usually utilizes a single ovoid implants and is anatomically indicated from the lumbar levels L1/L2 to L4/L5, whilst it is avoided at the L5/S1 level. [ 7 ] Indications for XLIF combined with posterior fixation include lumbar spinal stenosis and adjacent segment disease.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 , 27 ] Despite these advantages, XLIF has been also associated with a considerably higher frequency of neurological complications and other major morbidity. [ 28 ] XLIF usually utilizes a single ovoid implants and is anatomically indicated from the lumbar levels L1/L2 to L4/L5, whilst it is avoided at the L5/S1 level. [ 7 ] Indications for XLIF combined with posterior fixation include lumbar spinal stenosis and adjacent segment disease.…”
Section: Introductionmentioning
confidence: 99%
“…22,25 Neurological complications associated with lateral approaches are frequently discussed in the literature. 5,18 Previous anatomical and radiographic evaluations have identified that the lumbar plexus migrates dorsally to ventrally from L2-3 as the lumbosacral plexus descends caudally to the L4-5 and L5-S1 levels. 3,10,30 The underlying anatomical arrangement can endanger the lumbosacral plexus in a transpsoas approach to the L4-5 level.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,15,25,27 However, concerns exist about the rate of neurological complications associated with the lateral approach. 5,10,14,24 Furthermore, these complications are most conspicuous at the L4-5 level due to the anatomical arrangement of the lumbar plexus with narrower safe working zones more inferiorly in the lower lumbar spine. 30 Anterolisthesis at the L4-5 level serves to exacerbate this risk.…”
mentioning
confidence: 99%
“…Epstein showed minimal invasive surgeries (TLIF, PLIF, ALIF, LLIF) has a higher incidence of root injuries, radiculitis or plexopathy [33][34][35]. He recommended LLIF was not safe, and we should stop this procedure.…”
Section: Neurological Complicationsmentioning
confidence: 99%